Competence development as normative practice - Educational reform in medicine as heuristic model to relate worldview and education - Glas, Gerrit (Koers, 2012)
In this article, a Normative Practice Model (NPM) for education was developed. Two hypotheses guided this article: (1) the presupposition that developments in medical education are relevant for education in general and (2) the idea that medical education, just as education in general, can be interpreted as a normative practice. The Normative Practice Model was initially designed for medicine. This original version attempted to clarify why norms and values are intrinsic to medical practice, what these norms and values are, and how they are related. This article introduced the recent reform of medical specialist training programmes in the Netherlands as a case study for application of the Normative Practice Model to education. This reform elucidates how and why norms and values are intrinsic to medical education. The Normative Practice Model offers a global framework that enables one to locate and evaluate the relative contribution of each of the norms and values. By doing so the model also gives an answer to the more general question of whether and how worldview and education are connected. It appears that in highly technical and specialised practices such as medicine, the concept of competence is used as bridge between valued-laden motivations and attitudes on the one hand and measurable performance on the other hand. In this article it was argued that thinking about competences in the context of normative practices helps to elucidate the relationship between worldview and education.